Types of metaphors and the usage of them in literary texts - U. M. Mikhlieva; D.K. Bakhronova (Genius Publishing Group, 2023)
This article deals with metaphor in terms of its types and usage in literature. Particular attention is paid to the analysis of use of metaphors in the literary texts. It also provides several examples of metaphors in different writers’ works with classifications
Keywords: metaphor; language device; comparison